The ability of second grade students of SMA Adabiah Padang in Writing Analytical Exposition Text - Elfira Elfira; Yenni Rozimela; Delvi Wahyuni (Journal of English Language Teaching, 2018)
Analytical exposition text is one of the compulsory texts which is taught in senior high school in Indonesia. The aim of this research is to analyze how good students’ ability and describe students’ difficulties in writing analytical exposition text. It was a descriptive research. The population of this research is the second grade students of SMA Adabiah Padang, it were 48 students as the sample: XI IPA 1 which consists of 22 students and others form XI IPS 4. The students were asked to write an analytical exposition text. The students’ writing was analyzed by using the criterion published by Weston High School’s writing rubric which consists of five indicators: the introduction, body paragraphs and examples, conclusion, mechanics, and grammar and word choice. Based on the findings, most of the students get poor ability in four indicators measured: the introduction, body paragraphs and examples, conclusion, and mechanics and get good ability in the grammar and word choice.